Laparoscopic resection for spontaneously ruptured primary extragastrointestinal stromal tumor of the greater omentum: A case report. (October 2022) - Murata, Takaaki; Ishimori, Takahiro; Naitou, Wataru; Igrashi, Yuto; Suno, Yuma; Kawachi, Jun
Abstract: Introduction: Ruptured extragastrointestinal stromal tumor (EGIST) are rare; therefore, there are no standard guidelines for its treatment. Herein, we report the successful laparoscopic resection of a ruptured EGIST. Presentation of case: The patient was a 59-year-old man, a Jehovah's Witness, who presented with sudden onset of left-sided abdominal pain. Contrast-enhanced computed tomography (CECT) performed from a previous hospital revealed intra-abdominal hemorrhage. Repeat CECT at our institution revealed extravasation and serum ascites. A hematoma was found anterior to the omentum, and a tumor was detected which did not have continuity with the surrounding organs of the gastrointestinal tract. Complete tumor resection via laparoscopic surgery was performed and the specimen was sent for histopathology, which revealed bundle-like proliferation of spindle-shaped cells. Immunohistochemical staining was completed, which was positive for KIT and CD34. Based on surgical and pathological findings, the final diagnosis was extragastrointestinal stromal tumor originating from the omentum. Discussion: EGISTs have a similar morphology to that of gastrointestinal stromal tumors, but instead, arise outside the gastrointestinal tract. A significant differentiation and key to the diagnosis of EGIST is the absence of continuity with the gastrointestinal tract. The preferred treatment for EGIST is complete surgical resection, and the use of laparoscopy has not been well studied. Postoperative histopathological examination, along with immunohistochemical staining, aid confirmatory diagnosis. Conclusion: Laparoscopic removal of EGISTs is a minimally invasive and potentially useful technique for the management of this tumor type. Highlights: Diagnosis and treatment of a spontaneously ruptured tumor is complicated. Religion restrictions in management should be respected and followed. First line of treatment of EGISTs is complete surgical resection. Laparoscopic removal of EGISTs is minimally invasive and potentially useful.